Spinal cord tumors. Anatomoclinical study. - Pereirinha, R; Pimentel, J; Antunes, J L (Acta Médica Portuguesa, 1992)
The authors review 36 cases of intramedullary spinal tumours, 17 ependymomas, 12 astrocytomas, 6 hemangioblastomas and 1 metastasis of leiomyosarcoma. The tumours were localized in the cervical region in 19 patients, in the thoracic region in 10 in the lumbar region in 4, and in the conus medullaris in 3. All patients presented a clinical picture of myelopathy. No differences were observed between the different hystological types. In 5 patients the tumour was associated with syringomyelia and one of these patients also presented a type I Chiari malformation. All patients were submitted to surgery (using microsurgical techniques in the last seven years). Radiation therapy was also given in 16 cases. Our results demonstrate that microsurgical resection is the only treatment that significantly improves the prognosis of these patients, from both the standpoint of the functional status and survival.